2021
DOI: 10.1200/jco.20.01665
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cystectomy Against Intravesical BCG for High-Risk High-Grade Nonmuscle Invasive Bladder Cancer: Results From the Randomized Controlled BRAVO-Feasibility Study

Abstract: PURPOSE High-grade nonmuscle invasive bladder cancer (HRNMIBC) is a heterogeneous disease. Treatments include intravesical maintenance Bacillus Calmette-Guerin (mBCG) and radical cystectomy (RC). We wanted to understand whether a randomized trial comparing these options was possible. MATERIALS AND METHODS We conducted a two-arm, prospective multicenter randomized study to determine the feasibility in Bacillus Calmette-Guerin-naive patients. Participants had new high-risk HRNMIBC suitable for both treatments. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 28 publications
1
45
0
1
Order By: Relevance
“…However, the survival data of adjuvant treatment with an immune checkpoint inhibitor in NMIBC are still unknown. Catto et al performed a randomized controlled trial that showed that patients with high-risk NMIBC would have more clinical benefits after radical cystectomy compared with the TURB plus BCG group [ 11 ]. In our study, the 10-year CSS rate of included patients was 92.24%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the survival data of adjuvant treatment with an immune checkpoint inhibitor in NMIBC are still unknown. Catto et al performed a randomized controlled trial that showed that patients with high-risk NMIBC would have more clinical benefits after radical cystectomy compared with the TURB plus BCG group [ 11 ]. In our study, the 10-year CSS rate of included patients was 92.24%.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse reactions in both groups were mild [15/23 (65.2%) BCG vs 13/20 (65.0%) RC] with similar quality of life. The results showed that a considerable number of patients were suitable for bladder preservation and could contribute to health and quality of life ( 104 ).…”
Section: Clinical Application Of Bacteria-based Cancer Vaccinementioning
confidence: 99%
“…This may reflect the biology of the disease, healthcare behaviour of the at risk population [5] or that treatment improvements are needed. With regards to the latter, current pathways for BC patients can be slow and fail to discriminate between nonmuscle invasive (NMIBC) and muscle-invasive cancers (MIBC) [6,7]. For patients with MIBC, guidelines recommend that RC should not be delayed for longer than 12 weeks (84 days), as longer delays have significant impact on survival [8].…”
Section: Management Considerationsmentioning
confidence: 99%